Ministry of Trade and Industry Decree No. 257 of the year 2010 = وزارة التجارة والصناعة قرار رقم 257 لسنة 2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.